Penerapan Data Mining Untuk Memprediksi Minat Siswa Yang Mendaftar Di SMK Al Amin Cibarusah - Ermanto Ermanto (Teknik Informatika, Universitas Pelita Bangsa, 2021)
The level of interest of students who will enroll in Vocational High School (SMK) Al Amin Cibarusah can be estimated by using data mining methods. In order to find some information in a very large data, accurate algorithmic method is required. Several methods that are found very accurate in predicting and classifying and are often used are the Naive Bayes method, Nearest neighbor and Decision tree or J48. The author's focus in this study is to analyze the application of the Naive Bayes algorithm, Nearest neighbor and the J48 algorithm in predicting the interest of students who want to enroll in the Al Amin Cibarusah Vocational High School (SMK). The results obtained can be applied in making certain decisions and school policies. Keywords: Data mining, Naive bayes, Nearest neighbor, Decision tree and J48 Algorithm